보건의료인력 양성 프로그램의 만족도에 대한 질적 연구: 이종욱펠로우십 프로그램 임상과정(캄보디아 재활)을 중심으로 - 김유미; Youmi Kim; 김완호; Wanho Kim; 김은주; Eunjoo Kim; 정혜진; Hyejin Jung; 김수진; Soojin Kim; 김온유; Onyoo Kim (Health policy and management, 2023)
Background: We aimed to provide basic data for improving the effectiveness of the invitational training and reflecting it in the program in the following year by identifying the satisfaction level of trainees who participated in the “Dr. LEE Jong-wook Fellowship Program” funded by the Korea Foundation for International Healthcare. Methods: A qualitative study was conducted using a questionnaire interview. In the first stage of analysis, only the interview contents related to the research topic were classified by the researcher for the conversations recorded at the interview site, and in the second stage of analysis, the interview contents classified in the first stage were classified into each of those mentioned in this study. Results: The longer the trainees participated in the program and the better the accessibility, the higher the satisfaction with the program. In addition, the level of achievement of the trainees’ goals and the level of improvement in their competence affected their satisfaction, and their difficulty in language communication during the training period was identified as a factor affecting the trainees’ satisfaction level. In addition, competency improvement and satisfaction were positively correlated (r=0.75, p=0.03). Conclusion: When organizing a rehabilitation workforce capacity training program, it is important to identify trainees’ needs, ensure accessibility, organize courses effectively, enhance English proficiency, and expand practical lectures to increase trainees’ knowledge and understanding of rehabilitation.